Thick Individuality Within Thin Sense of Public Confusion within the Battle Against Corruption - Purwo Santoso (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2013)
Various concepts, models or theoretical frameworks are on offer, to frame the public in fighting against corruption in Indonesia. They include: bureaucratic reform, good governance, civil society engagement etc. In response to the failure to bring corruptionfree status, experts unnoticeably tend to blame public officers instead of ensuring the accuracy and the reliability of the framework. This reflective literature review reveals such tendency. To begin with, it maps out the logical basis of each approach, particularly in conceptualizing the ‘public’, the ‘private’, and their relationship. The reliability of the approaches will emerge as we link the conceptualization with real life the public or socio-cultural context. The review reveals that analysis on corruption and its imperative are ideologically driven, and hence, suffers from ideological bias. It obsesses with altering the behaviour of public officers, which inevitably entrapped with particular set-up. As liberal discourse take place in non-liberal institutional set-up, the public fail to comprehend the nature of the problems and the solution on offer. Instead of setting up context-specific agenda, public a dragged on various forms of reform such as granting political rights, enhancing civil society, articulate more autonomy and alike. As overwhelming individual within the battles against corruption overloaded with asserting of more public role, they encountered with difficulty in setting the boundary between the public and the private. As Indonesia has been endowed with different institutional set-up in governing public affairs, corruption-free public governance remains elusive. This is because the reforms dismantle the existing powerbase, which actually is vital for winning the fight against corruptive system.